Analisis Penggunaan Variabel Intervening Terhadap Variabel Endogen (Kasus Pada UMKM “X”) - Cicih Ratnasih (Fakultas Ekonomi Universitas Borobudur, 2016)
Based on the results of research and discussion on the intervening variable analysis of customer satisfaction and its impact on the endogenous variables that influence customer loyalty which are of variable quality of the product, price, and quality of service simultaneously towards customer satisfaction by 53.7%.There is a partial effect of variable product quality to customer satisfaction direct effect and indirect influence, there is a partial effect of variable price to customer satisfaction, direct effect and indirect effect of 14.6%. There is a partial effect of variable quality of service, to customer satisfaction, direct effect and indirect effect of 24.7%. There Effect of intervening variables that customer satisfaction to customer loyalty amounted to 54.5%. In this study that the intervening variables to get the total value of highest impact, when compared with the exogenous variables on the intervening variables. Key words: intervening variable analysis, customer satisfaction, customer loyalty, and endogenous variables.